Single‐Crystalline MFI Zeolite with Sheet‐Like Mesopores Layered along the a Axis. Issue 3 (11th December 2018) - Zhang, Yunjuan; Shen, Xuefeng; Gong, Zheng; Han, Lu; Sun, Huai; Che, Shunai
Abstract: Designing a templating strategy for directing mesopore growth along different crystallographic directions is essential for fabricating two‐ or three‐dimensional single‐crystalline mesoporous zeolites. However, so far, mesopores formed in MFI zeolites by soft templates have mostly been generated by disrupting growth along the b axis; generating mesopores by disrupting growth along the a axis is rare. Herein, a single‐crystalline mesoporous MFI zeolite (SCMMZ) with sheet‐like mesopores layered along the a and b axes was synthesized using a triply branched surfactant with diquaternary ammonium groups connected to 1, 3, 5‐triphenylbenzene by a six‐ and eight‐carbon alkyl chain (TPB‐6 and 8). The sheet‐like mesopores were embedded in the MFI framework and were retained even after calcination. Molecular mechanics calculations provided evidence of low binding energy configurations of the surfactant that directed the growth of straight and zigzag channels along the b and a axes, respectively. The formation of nanosheets was attributed to the geometric matching of the arrangement of the aromatic groups to the zeolite framework. Abstract : A single‐crystalline mesoporous MFI zeolite with sheet‐like mesopores layered along the a and b axes was templated by a triply branched surfactant with diquaternary ammonium groups connected to 1, 3, 5‐triphenylbenzene by a six‐carbon alkyl chain. The sheet‐like mesopores were embedded in the MFI framework and were retained even after calcination (see figure).